2021
DOI: 10.3390/v13061059
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Public RNA-Sequencing Data from Human Intestinal Enteroid (HIEs) Infected with Enteric RNA Viruses Identifies Universal and Virus-Specific Epithelial Responses

Abstract: Acute gastroenteritis (AGE) has a significant disease burden on society. Noroviruses, rotaviruses, and astroviruses are important viral causes of AGE but are relatively understudied enteric pathogens. Recent developments in novel biomimetic human models of enteric disease are opening new possibilities for studying human-specific host–microbe interactions. Human intestinal enteroids (HIE), which are epithelium-only intestinal organoids derived from stem cells isolated from human intestinal biopsy tissues, have … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 53 publications
(82 reference statements)
3
9
0
Order By: Relevance
“…Last, we wanted to explore whether this model would also provide insights in viral-host interactions and to this end, we performed an RNA sequencing analysis. Previous studies on enteric virus infection of enteroids unequivocally showed a signature dominated by interferon and innate immune pathways (7). Usually, interferon responses are initiated by infected cells but mostly amplified by bystander cells (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Last, we wanted to explore whether this model would also provide insights in viral-host interactions and to this end, we performed an RNA sequencing analysis. Previous studies on enteric virus infection of enteroids unequivocally showed a signature dominated by interferon and innate immune pathways (7). Usually, interferon responses are initiated by infected cells but mostly amplified by bystander cells (6).…”
Section: Discussionmentioning
confidence: 99%
“…The induction of the host innate response plays an essential role in the suppression of pathogen infection. In the case of enteric pathogens, interferon responses are highly upregulated in vivo and in vitro (6,7). We previously reported that human astrovirus VA1, another enteric virus and causative agent of viral gastroenteritis, induces interferon and interferon-stimulated genes (ISG) in the HIE system but not in an immortalized cell line, the Caco2 cells (8).…”
Section: Introductionmentioning
confidence: 99%
“…Transcription factor enrichment analysis of HNoV GII.4-infected HIEs identified STAT1 and STAT2 binding sites as highly enriched in the promoter regions of genes whose levels of expression were significantly upregulated following infection (41). Similarly, HNoV GII.4 infection of HIEs stimulates a robust innate response involving predominately a type III IFN response and the induction of ISGs including ISG15 and ISG45 (28,42). Targeted profiling of immunological genes associated with HNoV replication in HIEs suggests that the two most upregulated immune-related genes with viral replication are ISGs CXCL10 and IFI44L (43-45).…”
Section: Hnov Cultivation and Ifn Responses In Hiesmentioning
confidence: 99%
“…The understanding of HAstV pathogenesis has evolved with the development of relevant models for replication in cell lines (21,(70)(71)(72). Additionally, the recent identification of murine astrovirus (muAstV) as an endemic virus in mouse facilities (71) and HIE culturing methods for HAstVs have resulted in important advancements in HAstV pathobiology (21,28,73). MuAstV preferentially replicates in the small intestine and chronically infects immunocompromised mice (21,22,71), and some strains have been found to induce chronic antiviral signaling via type III IFN, supporting important interactions between AstVs and IFN signaling.…”
Section: Human Astrovirusmentioning
confidence: 99%
See 1 more Smart Citation